How to Identify the Subsurface Layer of Bangkam Hill - Mempawah Regency? Application of the Geoelectrical Resistivity Method - Ivansyah, Okto; Dilnalsyah, Felas; Sampurno, Joko; Muhardi, Muhardi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Mapping the subsurface is essential in rock exploration for construction to minimize costs and guide adequate mining planning. This study aims to identify the subsurface layer of Bangkam Hill, a depot of various rocks for construction materials located in Sungai Kunyit District, Mempawah Regency. A resistivity method was applied to map the sub-surface using the Wenner-Schlumberger configuration. Data acquisition was performed at six measurement lines to cover the hill. The results show that the subsurface layers of the hill from the ground to 40 m in depth are composed of sand, laterite soil, gravel, and igneous rock, with resistivity varying from about 30 to 693,055 Ωm. Using the subsurface map, the stakeholder can assess shallow rock reserves in the study area and create a proper mining strategy.